Indigenous mountain people's risk perception to environmental hazards in border conflict areas. (April 2019) - Ahmed, Bayes; Sammonds, Peter; Saville, Naomi M.; Le Masson, Virginie; Suri, Kavita; Bhat, Ghulam M.; Hakhoo, Naveen; Jolden, Tsering; Hussain, Gulzar; Wangmo, Kuenga; Thusu, Bindra
Abstract: This study aims to understand community risk perception to environmental hazards in a border conflict zone context in high-mountain areas. Participatory rural appraisal (PRA) tools were applied by the social science team. The results were validated with a hazard map prepared by a separate team comprised of geologists. Turtuk, the northernmost village in Ladakh, India located near the line of control with Pakistan was undertaken as a case study. Turtuk represents a high mountain indigenous rural community which has experienced several catastrophic disasters (flash flooding and landslides in 2010, 2014, and 2015) and territorial armed conflicts (wars in 1971 and 1999 with Pakistan) in recent times. The villagers were able to identify various environmental hazards and associated risk zones through participatory timeline diagram, and hazard and dream mapping exercises. The PRA maps matched the geological hazard map of Turtuk, demonstrating that community people are highly aware of surrounding hazards regardless of differences in age, sex, education, occupation, and religion. They apply indigenous knowledge to deal with the adverse climate and calamities. The technique, of analysing community vulnerability in the context of conflict and disasters by applying qualitative PRA tools and validating the mapping results, as piloted in this study is novel and replicable in any disaster setting. Highlights: Understanding community vulnerability in the context of disasters and conflict. Application of participatory hazard and dream mapping in analysing community risk perception. The high mountain communities in Ladakh are resilient to environmental hazards. They incorporate traditional and indigenous cultural knowledge. They need assistance to develop a risk-sensitive land use plan.